A MODERN INTERPRETATION OF THE PROBLEM: GENETIC PPREDISPOSITION TO OUT-OF-HOSPITAL PNEUMONIA IN CHILDREN - Normamatov D.X; Fayzieva U.R; Abdurasulova T.D; Djumaev A.A; Xolboev N.A. (Scholar Express Journals, 2021)
The article provides a review of the literature devoted to modern data, as well as the impact of genetic predisposition on the development of pneumonia in children. It is known that timely, innovative diagnosis, treatment and prevention of pneumonia in children today is one of the most pressing problems in pediatrics. Timely identification of the etiological cause of pneumonia, treatment is carried out only by early diagnosis, adequate assessment of the severity of the patient's condition, reasonable choice of treatment with antibiotics, taking into account the background disease, age and weight ofthe child
Keywords: Pneumonia; children; genes; predisposition